2012
DOI: 10.1007/s13181-012-0252-0
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Exposure Among Artisanal Gold Miners in Madre de Dios, Peru: A Cross-sectional Study

Abstract: Introduction Exposure to mercury, a toxic metal, occurs primarily from inhaling mercury vapors or consuming methylmercury-contaminated fish. One third of all anthropogenic mercury emissions worldwide are from artisanal gold mining, which uses mercury to extract gold. Although recent reports suggest that the Madre de Dios region in Peru (with >30,000 artisanal miners) has extensive mercury contamination, residents had never been assessed for mercury exposure. Thus, our objective was to quantify mercury exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 15 publications
1
56
1
4
Order By: Relevance
“…A study of 103 ASGM miners in Madre de Dios in 2010 found that all participants had detectable levels of mercury in urine, and 91% had detectable levels of blood methylmercury [45]. As with the study by Ashe (2012) [44], Yard et al (2012) [45] found that higher fish consumption was associated with increased hair mercury levels; Yard et al further found that exposure to heated gold-mercury amalgam was correlated with higher mercury levels.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…A study of 103 ASGM miners in Madre de Dios in 2010 found that all participants had detectable levels of mercury in urine, and 91% had detectable levels of blood methylmercury [45]. As with the study by Ashe (2012) [44], Yard et al (2012) [45] found that higher fish consumption was associated with increased hair mercury levels; Yard et al further found that exposure to heated gold-mercury amalgam was correlated with higher mercury levels.…”
Section: Discussionmentioning
confidence: 88%
“…A 2012 study on the mercury levels in human hair among 104 participants in the town of Puerto Maldonado in Madre de Dios and 100 participants in an ASGM mining zone in the region, found that residence location and sex were correlated with higher mercury levels, and that the total levels of mercury in hair were significantly higher in the mining zones [44]. A study of 103 ASGM miners in Madre de Dios in 2010 found that all participants had detectable levels of mercury in urine, and 91% had detectable levels of blood methylmercury [45]. As with the study by Ashe (2012) [44], Yard et al (2012) [45] found that higher fish consumption was associated with increased hair mercury levels; Yard et al further found that exposure to heated gold-mercury amalgam was correlated with higher mercury levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several research related to the impact of the use of mercury in artisanal gold mining had been done around the world ( [5], [6], [7], [8], [9]). In Indonesia, research on artisanal gold mining had been conducted ( [10], [11], [12], [13], [14]) but it is still limited on research topic related to the impact of mercury on neurological disturbances.…”
Section: Introductionmentioning
confidence: 99%